Stereocomplex crystallization, homocrystallization, and polymorphism of enantiomeric copolyesteramides poly(lactic acid‐co‐alanine)s from the melt. Issue 2 (19th November 2019) - Tsuji, Hideto; Sato, Shotaro; Masaki, Noriaki; Arakawa, Yuki; Yoshizaki, Yuta; Kuzuya, Akinori; Ohya, Yuichi
Abstract: Stereocomplex (SC) crystallization, homocrystallization, and polymorphism of poly(l ‐lactic acid‐ co ‐l ‐alanine) [P(LLA‐LAL)] and poly(d ‐lactic acid‐ co ‐d ‐alanine) [P(DLA‐DAL)] copolymers with wide alanine unit content ranges from 0 to 21 and 22 mol% are investigated for melt‐crystallization. P(LLA‐LAL)/P(DLA‐DAL) blends crystallize for wide alanine unit content ranges compared to unblended P(LLA‐LAL) and P(DLA‐DAL) samples, due to facile SC crystallization compared to homocrystallization. The phase diagrams of the unblended samples [ α‐ and δ ‐form homocrystallites] and the blend samples (SC and homocrystallites) are drawn. The transition crystallization temperature of unblended samples from α ‐form to δ ‐form decreases with an increase in alanine unit content. In the unblended and blend samples, alanine units are correspondingly incorporated in α ‐form homocrystalline regions and excluded from SC crystalline regions. The maximum radial growth rate values of spherulites are higher for the blend samples than for the unblended samples. The experimental crystallization half time [ t c (1/2)(exp)] values of the unblended samples increase with an increase in alanine unit content, whereas the t c (1/2)(exp) values of the blend samples with alanine unit contents of 3 and 4 mol% and 6 and 6 mol% and of 12 and 13 mol% are respectively higher than and similar to those of poly(l ‐lactic acid)/poly(d ‐lactic acid) blend. Abstract : Stereocomplex crystallization, homocrystallization, and polymorphism of enantiomeric copolyesteramides poly(l ‐lactic acid‐ co ‐l ‐alanine) [P(LLA‐LAL)] and poly(d ‐lactic acid‐ co ‐d ‐alanine) [P(DLA‐DAL)] copolymers with wide alanine unit content ranges from 0 to 21 and 22 mol% were investigated for melt‐crystallization by wide‐angle X‐ray diffractometry and polarized optical microscopy. The effects of incorporated alanine units and crystallization temperature on the crystalline species, crystallinity, crystallization rate, crystalline growth geometries, and kinetics are discussed in detail.